Pour une approche génétique de L’Éducation sentimentale (1869) : état présent, perspectives, démarches - Déborah Boltz (Flaubert: Revue Critique et Génétique)
The genetic dossier of L’Éducation sentimentale (1869), almost complete but dispersed in several public institutions, has been open to research for the last thirty years. During this time the genetic approach to this manuscript corpus has produced numerous works, mainly by ITEM researchers. To this should be added two important works in progress: first, the research begun in 2006 for the online edition of the “Flaubert” corpus, in the framework of the ANR program titled “OPTIMA” (Outil pour le traitement et l’analyse de l’information dans les manuscrits modernes / Tool for the treatment and analysis of information in modern manuscripts) of which ITEM is in charge, and which features the classification and transcription of the Éducation sentimentaledrafts. Secondly, the editorial project of volume IV of the Complete Works of Flaubert in the “Pléiade” edition devoted to the Parisian novel. In view of these two works in progress on the text and the “avant-texte” of L’Éducation sentimentale, the time has come to draw up a critical and descriptive evaluation of the work produced on this corpus. How far have we gone in the genetic approach to this dossier? What has been studied in the “avant-textes” as well as in the “printed genetics”? And what, on the contrary, has remained unexplored? Finally, what can we expect of a major renewal in the reading and interpretation of this work?